Through the looking glass: leadership in the age of surveillance - Keim, Charles; Shadnam, Masoud (My University, 2018)
The last few decades have witnessed a dramatic rise in the use of surveillance, particularly in organizational life (Anteby & Chan, 2018). Primary forms of surveillance, such as the supervisor’s gaze, are being augmented by sophisticated devices capable of tracking more than employees’ work habits: public and private affairs, past and present choices, opinions and attitudes are increasingly recorded, retained, and used to predict or shape future behavior. The technologies of surveillance, elaborate in their subtlety, inexpensiveness, and accessibility, coupled with the proliferation of individual devices (e.g., cell phones), are decentralizing a strategic tool previously the exclusive domain of the managerial elite. Hence, a vision of what the future of leadership holds must grapple with the increased surveillance leaders will face by those inside and outside of the organization. The ascendancy and proliferation of surveillance have significant implications for leadership. In this brief paper, we identify and discuss two core implications: first, surveillance systems will alter the criteria discriminating between future leaders—i.e., leader emergence will increasingly rest on individuals’ knowledge of what surveillance systems capture as well as their performative capacity to enact behaviors suited for those systems. Second, the effectiveness of leaders within a time of heightened surveillance will place a premium on the forbearance and flexibility of leaders to work with one another within an organizational field.
Keywords: surveillance; leadership; surveillance leaders; organizational field; performative capacity; surveillance systems; proliferation of surveillance